The Impact of Plasmodium Infection on Placental Histomorphology: A Stereological Preliminary Study - John Ahenkorah; Patience B. Tetteh-Quarcoo; Mercy A. Nuamah; Bethel Kwansa-Bentum; Hanson G. Nuamah; Bismarck Hottor; Emmanuel Korankye; Magdalene Torto; Michael Ntumy; Fredrick K. Addai (Hindawi Limited, 2019)
Background. Malaria during pregnancy may threaten the mother's health and cause serious structural damage to the internal architecture of the placenta, which subsequently affects the pregnancy outcome. A better understanding of the impact of malaria parasites on the placenta morphology is crucial for better management of pregnant women and their babies. Aim. To assess by stereology the histomorphology of selected placental structures in placenta malaria compared with normal placentae at term. Method. A total of 10 placentae comprising 5 controls and 5 cases were selected from 50 placentae that were collected at term (38 weeks ± 2 weeks) from the maternal delivery suit of Korle-Bu Teaching Hospital in Accra, Ghana. Blood from the placentae was collected for both rapid diagnostic test and microscopic examinations. Samples collected were examined for Plasmodium parasites, after which they were classified as study group (Plasmodium positive) or control (Plasmodium negative). Stereological quantification using systematic uniform random sampling technique with test point and intersection counting of photomicrographs were employed to estimate the mean volume densities of syncytial knots, syncytial necrosis, foetal capillaries, and intervillous spaces of the placentae on a total of 1,600 photomicrographs. Results. Out of the fifty placental samples from the maternal side tested for Plasmodium, six representing 12% were found to be infected with the parasite by both rapid diagnostic test and microscopy. On stereological assessment, the mean volume density of syncytial knots was significantly higher in the placental malaria group compared with the control placentae at term (P = 0.0080), but foetal capillaries (P = 0.7813), intervillous spaces (P = 0.8078), and syncytial necrosis (P = 0.8249) were not significantly different. Conclusion. This preliminary result indicates that placental malaria may cause significant increase in the syncytial knots but not foetal capillaries, intervillous spaces, or syncytial necrosis. This finding signifies early maturation of the placenta and may be crucial in understanding perinatal outcomes.